Full Scale Reinforced Concrete Beam-Column Joints Strengthened with Steel Reinforced Polymer Systems - De Vita, Alessandro; Napoli, Annalisa; Realfonzo, Roberto (Frontiers in Materials, 2017)
This paper presents the results of an experimental campaign performed at the Laboratory of Materials and Structural Testing of the University of Salerno (Italy) in order to investigate the seismic performance of RC beam-column joints strengthened with Steel Reinforced Polymer (SRP) systems. With the aim to represent typical façade frames’ beam-column subassemblies found in existing RC buildings, specimens were provided with two short beam stubs orthogonal to the main beam and were designed with inadequate seismic details. Five members were strengthened by using two different SRP layouts while the remaining ones were used as benchmarks. Once damaged, two specimens were also repaired, retrofitted with SRP and subjected to cyclic test again. The results of cyclic tests performed on SRP strengthened joints are examined through a comparison with the outcomes of the previous experimental program including companion specimens not provided with transverse beam stubs and strengthened by Carbon Fiber Reinforced Polymer (CFRP) systems. In particular, both qualitative and quantitative considerations about the influence of the confining effect provided by the secondary beams on the joint response, the suitability of all the adopted strengthening solutions (SRP/CFRP systems), the performances and the failure modes experienced in the several cases studied are provided.